Gangguan Berbicara Rhotacism Pada Anak Remaja (Kajian Psikolinguistik) - Sulthaanika Ferdy Syahwardi; Odien Rosidin (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
Researchers found slurred speech disorder (Rhotacism) in adolescents aged 13 and 15 years who have imperfections which have difficulty pronouncing /r/ to become /l/. This study aims to (1) describe Rhotacism's speech disorders, especially phonetic disorders in adolescents and (2) describe the causes of Rhotacism's disorders in adolescents. This study uses a qualitative descriptive research method and uses a case study approach with subjects or informants aged 13 and 15 years named Alden Nandana Ramadhan and Mauli Ibrahim who come from Serang Regency. The results showed that in Alden Nandana Ramadhan there were 6 data that experienced sound changes when pronouncing the letters /r/ to /l/. Meanwhile, in Mauli Ibrahim found 11 data that experienced sound changes when pronouncing the letter /r/ to /l/ and 1 omission of the letter /r/. The causes of Rhotacism speech disorders in children are caused by several factors, namely sufferers have siblings, aunts. Siblings with speech disorders, namely Rhotacism. Rhotacism speech disorders appear when toddlers, children, teenagers and even adults because of factors, namely angklossia (short tongue) which results in an impact on the imperfection of phonemes (sounds) spoken by speakers to speakers